Influence of irrigation and genotype on the nut production of precocious dwarf cashew - Oliveira, Vitor Hugo de; Barros, Levi de Moura; Lima, Raimundo Nonato de (Pesquisa Agropecuaria Brasileira, 2003)
The influence of irrigation and genotype on the nut yield of tree dwarf cashew (Anacardium occidentale L.) was evaluated in a three-year trial. Three clones (CP 09, CP 76 and CP 1001) and four irrigation treatments (control - without irrigation, irrigation at one, three and five days interval) were studied. The experimental design was in randomized blocks, with split-split plots and four replications, irrigation levels in plots, clones in split-plot, each one with four plants, and years of production in split-split plots. The amount of water applied in three irrigated treatments was based on information from a class A evaporation pan. Concerning cashew nut production, cashew dwarf clones did not show a differentiation as to irrigation treatments; clones CP 09 and CP 76 showed better performance than CP 1001 on stability of nut production; clone CP 76, independently of irrigation treatments used, showed less productivity than clones CP 09 and CP 1001.